2013
DOI: 10.1590/s0034-737x2013000300008
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de espécies bioindicadoras de resíduos de herbicidas auxínicos

Abstract: Determination of bioindicators of auxinic herbicides residuesHerbicides that present soil residual activity may become a problem in agricultural crops due to the possibility of crops successors intoxication. It is hard to detect residues of hormonal herbicides using the bioassay technique, due to the variation in the growth response of the indicator plant. The objective of this work was to select plants and variables susceptible to the herbicides 2,4-D and picloram for soil residue indication..To make it possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 12 publications
3
13
0
9
Order By: Relevance
“…This can affect the growth, productivity, and quality of vegetable crops that are commercialized (Hutchinson et al, 2007;Robinson and Mcnaughton 2012;Sousa et al, 2012;Riddle et al, 2013). Beets are highly sensitive to soil residues, the reason why they are used as a bioindicator species in trials with different herbicides (Szmigielski et al, 2009;Santos et al, 2013;Silva et al, 2014). The growth of beets is usually carried out in succession to the corn crop (Soltani et al, 2005), in which atrazine and tembotrione are frequently applied.…”
Section: Introductionmentioning
confidence: 99%
“…This can affect the growth, productivity, and quality of vegetable crops that are commercialized (Hutchinson et al, 2007;Robinson and Mcnaughton 2012;Sousa et al, 2012;Riddle et al, 2013). Beets are highly sensitive to soil residues, the reason why they are used as a bioindicator species in trials with different herbicides (Szmigielski et al, 2009;Santos et al, 2013;Silva et al, 2014). The growth of beets is usually carried out in succession to the corn crop (Soltani et al, 2005), in which atrazine and tembotrione are frequently applied.…”
Section: Introductionmentioning
confidence: 99%
“…Os herbicidas do grupo das auxinas sintéticas têm sido um dos mais usados no controle de plantas daninhas dicotiledôneas em forrageiras (BRAGA, 2013). Dentre os herbicidas deste grupo, o 2,4-D (ácido 2,4-diclorofenoxiacético) e o picloram (ácido 4-amino 3,5,6 tricloro-2-piridinacarboxílico) compõem a maioria dos produtos registrados para aplicação na agricultura (BRASIL, 2013).…”
Section: Introductionunclassified
“…Buscando-se encontrar formas de reduzir o risco do impacto ambiental que o efeito residual de herbicida possa vir a causar, além de minimizar problemas de fitointoxicação e perdas em culturas subsequentes, diversos estudos têm sido realizados especialmente para compreender o comportamento desses produtos no solo (SANTOS et al, 2013).…”
Section: Introductionunclassified
“…Various forage species, such as Eleusine coracana, brachiaria and Panicum maximum, have been used in picloram phytoremediation programs (Santos et al 2006, Belo et al 2007a, Carmo et al 2008aand 2008b, Pires et al 2008. Santos et al (2013) studied the sensitivity of three species (beet, cucumber and tomato) for 2.4 D and picloram to be used as indicators and concluded that beet and tomato are more sensitive, and the symptoms of visual intoxication ranged for assessing the presence of herbicide residues.…”
Section: Palavras-chavementioning
confidence: 99%